EDUCATION OF DEAF AND HEARING-IMPAIRED CHILDREN THROUGH ELECTRONIC EDUCATION PLATFORMS (Web of Teachers: Inderscience Research, 2025)
This article provides a comprehensive analysis of the pedagogical, psychological and technological aspects of teaching deaf and hard-of-hearing students through e-learning platforms. The study explores effective ways to expand the learning opportunities of students with hearing impairments and develop their speech and communicative competencies using digital technologies. The article covers aspects such as individual teaching of students through e-learning environments, the use of visual materials, and increasing motivation through game tasks. The article also analyzes the capabilities of platforms such as “Moodle”, “Google Classroom”, “iSpring Suite”, “H5P”, and presents methods for adapting them for students with special needs.